Screening and characterization of paclitaxel-producing fungus \(Talaromyces wortmannii\) WQF18 isolated from \(Cephalotaxus mannii \)Hook. f.. - Ngoc Tung, Quach; Hanh Nguyen, Vu Thi; Quynh Anh, Pham; Hong Quang, Tran; Hoang Ha, Chu; Quyet Tien, Phi (Academia Journal of Biology, 2023)
Cephalotaxus mannii Hook. f. is a rare evergreen conifer native listed in the International Union for Conservation of Nature (IUCN) Red List, which is utilized for leukemia treatment. Although endophytic fungi from C. mannii was reported before, their cytotoxic property has not been revealed yet. In the present study, a total of 7 endophytic fungi were isolated from C. mannii collected in Ha Giang province, Vietnam, among which the isolate WQF18 was active against 5 tested pathogens with inhibition zones ranging from 18.0 ± 0.7 to 25.0 ± 0.4 mm. In addition, only ethyl acetate extract of isolate WQF18 showed cytotoxicity on A549 and MCF7 cell lines with IC50 values of 69.6 ± 2.3 µg/mL and 78.6 ± 1.6 µg/mL, respectively. PCR-based molecular screening revealed that the positive hits for both 10-deacetylbaccatin III-10-O-acetyl transferase (dbat) and taxadiene synthase (ts) genes involved in paclitaxel biosynthesis were only observed in the WQF18 isolate. Based on morphological and molecular identification, the WQF18 isolate was identified as Talaromyces wortmannii WQF18. The presence of paclitaxel in T. wortmannii WQF18 was further confirmed by dbat sequence alignment, phenotypic, and HPLC-DAD analysis. To the best of our knowledge, this is the first report demonstrating the paclitaxel-producing capability of endophytic fungi from C. mannii. These findings provide a new platform for deciphering paclitaxel biosynthesis of endophytic fungi from non-Taxus plants and further paclitaxel production.